(untitled) (Research, Society and Development, 2023)
The present study aims to understand the scenario of hospital morbidity due to stroke, in Bahia, between January 2021 and July 2022. This is a descriptive, quantitative and epidemiological study. To carry out the research, data were collected electronically between the months of August and October 2022 on the Bahia platform through DATASUS, followed by access to the TABNET platform. After data collection, three tables were constructed. Table 1 shows that the number of hospitalizations due to urgency is greater than the number of elective admissions, the incidence by age group is in people aged between 50 and 80. In Table 2, it is noted that the female gender presents disparity compared to the male gender, corresponding to 51% of deaths and 50.1% of hospitalizations, the brown race stands out among the numbers of hospitalizations (58.2%) and deaths (59%). In tables 1, 2 and 3 of the results analyzed in 9 Bahian micro-regions, the East region, with emphasis on the city of Salvador, is in first place in the number of occurrences. During the research, gaps emerged that made it difficult to provide studies related to the topic. Investment in new studies enables decision-making with regard to public policies, reforming care strategies in specialization centers for stroke patients.